2011
DOI: 10.1159/000321273
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for the Smoking Cessation Role among Health Sciences Students in Kuwait

Abstract: Objective: Our aim was to assess students’ preparedness for the smoking cessation role after a teaching module on tobacco cessation and to assess the relationship between smoking status and preparedness. Methods: Pharmacy students attended a 4-hour module on the role of health professionals in smoking cessation based on the Rx for Change training program. Two years after the first introduction of the module, a questionnaire on preparedness and smoking status was filled in by 64 pharmacy students who had attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…Good practice was observed more among nonusers of tobacco as compared to current tobacco users but the difference was not significant. This is in accordance with other studies (24,33,34). By comparison, a study in Ontario showed that former smokers and never smokers were significantly more likely to have good practice than current smokers have (31).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Good practice was observed more among nonusers of tobacco as compared to current tobacco users but the difference was not significant. This is in accordance with other studies (24,33,34). By comparison, a study in Ontario showed that former smokers and never smokers were significantly more likely to have good practice than current smokers have (31).…”
Section: Discussionsupporting
confidence: 93%
“…Dentists who have never consumed tobacco had a significantly higher good attitude score than those that had ever been tobacco users. This finding is consistent with studies in Kuwait, Kenya and Finland that reported a negative attitude towards patient counselling about smoking among healthcare professionals who smoke compared to those who are nonsmokers (24)(25)(26). This provides insight into the fact that dentists hold strong beliefs that they serve as a role model to their patients (11,12).…”
Section: Discussionsupporting
confidence: 89%
“…Considering the fact that people find many friends at their university, it may follow that students smoke a water pipe as a way of spending their leisure time, and this may account for the higher prevalence of water pipe smoking among people with a university education. Educational interventions may be effective for helping smokers to quit [29]. …”
Section: Discussionmentioning
confidence: 99%
“…The latter is an oxidative stressinduced transcription factor that regulates the expression of a number of antioxidant genes [18]. Not surprisingly, smoking has for a long time raised concern in the AGCs [19][20][21].…”
Section: Dendritic Cells (Dc)mentioning
confidence: 99%